Informal Employment and Irregular Migration Status: A Double Whammy for Migrant Workers in Thailand - Ducanes, Geoffrey (Archīum Ateneo, 2023)
While a thick strand of literature demonstrates informally employed workers and irregular migrants being generally worse off in the labor market, little has been done to examine and compare these two sources of disadvantages. Using regression analyses on a survey of migrant workers in Thailand from Cambodia, Myanmar and Lao People’s Democratic Republic, the paper measures the prevalence of informal employment and estimates the differential contributions of irregular migration status and informal employment on various employment conditions. The paper finds that informality has a relatively stronger association with worse employment conditions, and systematic differences persist across sectors of employment and countries of origin. Initiatives to improve working conditions for irregular migrant workers should thus focus on both formalizing their employment status and expanding access to legal and safe migration, including social protection programs, in destination countries.